Contrasts in the multiple causes of stillbirth, neonatal death and postneonatal death. Issue 4 (December 1989) - Murphy, M; Botting, B
Abstract : A large sample of stillbirth and infant death certificates for England and Wales from 1979-81 was analysed for the frequency of appearance of maternal and fetal conditions anywhere on the certificate, not just as the underlying cause. The results suggest there is presently no need to extend the use of the new stillbirth and neonatal death certificates, introduced in 1986, to the postneonatal period. Periodic multicause analysis of the old style death certificate should be sufficient to reveal the detail of conditions incriminated in postneonatal deaths.